Stay clear with Pap smears - Law, Chloe Ying Tong (Nanyang Technological University, 2024)
Stay Clear with Pap Smears investigates the types of rational arguments and heuristic cues that are most effective for Pap smear campaign strategies among Singaporean women aged 23-29. Our research objectives are to [1] understand motivations and barriers towards getting Pap smears, [2] investigate the most persuasive ELM factors vis-à-vis Pap smears, and to [3] discover important factors beyond the ELM. In Study 1, focus group discussions (n=20) were carried out among women aged 23-29. Participants shared their thoughts about several ads and drew one they felt would be most persuasive to them. These activities were used to help identify salient factors that encouraged Pap smear uptake. However, as results were inconclusive, we conducted Study 2, comprising a 2-week Instagram campaign, employing a 2 (source: human/organisation; between-subjects) X 2 (information completeness: simple/complete; within-subjects) X 3 (fear: none/low/moderate; within subjects) mixed factorial design (n=214). Results showed that [A] information source did not significantly persuade our TA to get Pap smears [B] high information completeness was preferred and increased post persuasiveness and [C] low fear and no fear messages were most persuasive. Finally, we discussed practical uses of our findings to guide future womens’ health campaigns.